Intermittent respiratory obstruction secondary to an Antro Chonal polyp : a rare late presentation - Shashinder, S.; Kuljit, S.; Subha, Sethu Thakachy; Arumainathan, U. D.; Gopala, K. G. (Malaysian Medical Association, 2007)
We describe a child who presented with intermittent respiratory obstruction especially in supine position. Examination revealed a fleshy post nasal mass extending up to the oropharynx. The mass was removed surgically and histopathology revealed an antrochonal polyp. Patient was relieved of his symptoms and has been well ever since.